Advances in the Conversion of Furfural to Biofuels - Yingying XU; Xinhua QI (能源环境保护)
The application of biofuels could greatly alleviate energy crises and environmental problems caused by the overexploitation of fossil resources. Furfural is regarded as one of the highest value-added chemicals derived from biomass and serves as a key intermediate in biorefinery processes. It is widely used in the synthesis of plastics, pharmaceuticals, as well as various furan-based fine chemicals and biofuels. Furfural derivatives, such as furfuryl alcohol, tetrahydrofurfuryl alcohol, 2-methylfuran, levulinates, furfuran ether, and γ-valerolactone, have great potential as biofuels or fuel additives due to their high energy density and octane ratings. Furthermore, the study of furfural conversion into biofuels could significantly alleviate the energy crisis and align with the national strategies for achieving "carbon peak" and "carbon neutrality". The production of furfural-derived compounds involves a series of reactions, including hydrogenation, hydrodeoxygenation, alcoholysis, and cascade transformations. These processes result in a variety of furfural-based compounds with distinct fuel properties. Furfuryl alcohol, the primary hydrogenation product of furfural, demonstrates good renewability and moderate calorific value. Tetrahydrofurfuryl alcohol offers excellent thermal stability and heating value, making it a promising candidate as a fuel additive. 2-Methylfuran stands out for its high energy density and octane number, delivering superior combustion performance compared to ethanol and significantly enhancing engine thermal efficiency. Levulinates (e.g., ethyl levulinate) possess favorable characteristics such as high lubricity, volatility, and oxygen content, which contribute to improved combustion efficiency and reduced particulate emissions. Furfuran ethers, with their high energy density and volatility, are suitable for use as gasoline additives to enhance octane rating and promote cleaner combustion. γ-Valerolactone, a chemically stable compound, functions effectively as a fuel additive by reducing carbon monoxide and particulate matter emissions, while also exhibiting strong environmental compatibility. Despite these advantages, furfural-derived biofuels face several limitations compared to commercial fossil-based fuel additives, including poor oxidative stability, inadequate cold-flow properties, and microbial degradation. Addressing these issues by enhancing oxidation resistance, improving low-temperature performance, and increasing storage stability is essential to advance the practical application and large-scale commercialization of these bio-based fuel additives. Although these biofuels hold significant promise, the conversion processes encounter several challenges, including low conversion efficiency, high energy demands, and complex reaction mechanisms. Consequently, future research should prioritize the development of more efficient and environmentally sustainable catalytic systems. In addition, optimizing reaction conditions, such as reducing the temperature and pressure requirements, is crucial for enhancing overall energy efficiency. Furthermore, establishing continuous production systems will be essential for scaling up the industrial production of biofuels. Progress in these areas will be vital for improving the economic viability of biofuels and facilitating the transition to a more sustainable, carbon-neutral energy future.